Relationship between catalase and glycolate oxidase activities in response to contrasting photorespiratory conditions induced by different light intensities - Patriota, Maiany Alves (2022)
Glycolate oxidase (GO) and catalase (CAT) are two crucial enzymes involved in photorespiratory metabolism in higher plants. Although GO is the only plant enzyme capable of eliminating the glycolate accumulated by the oxygenase activity of Rubisco, its reaction has the side effect of producing hydrogen peroxide (H2O2) in peroxisomes that must be quickly removed by CAT activity. In fact, the co-evolutionary need for a functioning of these enzymes has been considered in the literature and recent studies point to a possible interaction between these proteins forming a large enzyme complex. Despite this interaction, the physiological significance of crosstalk between GO and CAT is still poorly understood, especially under contrasting photorespiration conditions. Thus, the present study aimed to investigate the possible functional regulation between GO and CAT in rice plants exposed to different photorespiratory levels, induced by light variations. For this, in a first experiment, rice seeds (Oryza sativa japonica cv. Nipponbare) were cultivated in a greenhouse for 40 days. Photorespiration and photosynthesis were characterized by in vivo measurements using an infrared gas analyzer(IRGA). The activity of GO and CAT enzymes, the content of substances reactive to tiubarbituric acid (TBARES), the accumulation of H2O2 and redox levels of ascorbate and glutathione were also determined. The results showed a decrease in photosynthesis and an increase in photorespiration with increasing light. The activity of GO and CAT increased under photorespiratory condition and were positively correlated to each other. In addition to the cross-talk of the enzymes among themselves, both are strongly related to the H2O2 pool, as well as to membrane damage and lipid peroxidation caused by it, even as respond in an negative-correlated manner to the ASC-GSH cycle .